International collaborative study for establishment of the 2nd WHO International Standard for Haemophilus influenzae type b polysaccharide. Issue 6 (November 2015) - Mawas, Fatme; Burkin, Karena; Dougall, Thomas; Saydam, Manolya; Rigsby, Peter; Bolgiano, Barbara; ,
Abstract: In this report we present the results of a collaborative study for the preparation and calibration of a replacement International Standard (IS) for Haemophilus influenzae type b polysaccharide (polyribosyl ribitol phosphate; 5-d -ribitol-(1 → 1)-β-d -ribose-3-phosphate; PRP). Two candidate preparations were evaluated. Thirteen laboratories from 9 different countries participated in the collaborative study to assess the suitability and determine the PRP content of two candidate standards. On the basis of the results from this study, Candidate 2 (NIBSC code 12/306) has been established as the 2nd WHO IS for PRP by the Expert Committee of Biological Standards of the World Health Organisation with a content of 4.904 ± 0.185 mg/ampoule, as determined by the ribose assays carried out by 11 of the participating laboratories.